A comparison between quantitative gated myocardial perfusion scintigraphy and strain echocardiography as indicators of ventricular functions in patients with anterior myocardial infarction - Seyhan Karacavus; Ahmet Celik; Ahmet Tutus; Mustafa Kula; Abdurrahman Oguzhan; Ibrahim Ozdogru; Nihat Kalay (World Journal of Nuclear Medicine)
The purpose of this study is to compare the strain echocardiographic and scintigraphic parameters for evaluating of the left ventricular (LV) functions in patients with anterior myocardial infarction (MI). Fifty-four patients (male/female: 36/18; mean age 62 ± 13 years) with anterior MI were prospectively enrolled. All patients were performed gated myocardial perfusion scintigraphy gated single-photon emission computed tomography (GSPECT) and echocardiography (EC). GSPECT data were processed and analyzed using 4D-MSPECT (4DM, Invia Medical Imaging Solutions, Ann Arbor, MI, USA). The echocardiographic strain (S) and strain rate (SR) values were calculated. The results obtained by these techniques were compared each other. A total of 918 segments of LV wall were evaluated. In all patients, 385 segments were automatically scored as normokinetic, 206 as hypokinetic, 122 as akinetic, 205 as dyskinetic and 300 as normal thickening, 348 as decrease thickening and 270 as no thickening. The means of S and SR values in thickening and motion score groups according to GSPECT were statistically different from each other (P < 0.001). There was a negative significant correlation between LV wall thickening sum score and S and SR and between LV wall motion sum score and S and SR (P < 0.001). There was a good correlation between GSPECT and echocardiographic LV-ejection fraction (r = 0.7, P < 0.001). GSPECT and strain EC are similar in quantitative grading of the severity of regional and global myocardial dysfunction in patients with anterior MI and these techniques provide valuable diagnostic information.